For the thrill of it Leopold, Loeb, and the murder that shocked jazz age Chicago - Baatz, Simon (Harper Perennial, 2009)
In the tradition of "The Devil in the White City" comes a riveting recreation of one of the most infamous crimes of the 20th century--the scandalous Leopold-Loeb murder case that shocked Chicago. Photos throughout.